Correction: The effect of morphology on electrochemical hydrogen evolution reaction of ReSe2 nano-structures. (7th October 2022) - Sultana, Fozia; Mushtaq, Muhammad; Ferdous, Tabassum; Wang, Jiahui; Lin, Ma; Zaman, Abid; Althubeiti, Khaled; Aljohani, Mohammed; Yang, Qing
Abstract : Correction for 'The effect of morphology on electrochemical hydrogen evolution reaction of ReSe2 nano-structures' by Fozia Sultana et al., New J. Chem., 2022, 46, 14894–14902, ; https://doi.org/10.1039/D2NJ02433K .